Análise de imagens para fins analíticos: aplicações ambientais e tecnológicas - Passaretti Filho, Juliano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work describes the development of sensitive, selective, and inexpensive methods with potential for use in environmental and technological applications. The techniques are based on reactions in aqueous solution that produce colored species that can be measured optically by means of the acquisition and processing of digital images. The experiments demonstrated the viability of using CMOS and CCD sensors to acquire digital images. In preliminary tests, comparison was made of analytical signals obtained using the digital image method and spectrophotometry, for measurements of nitrite, inorganic phosphate, and residual ozone in water. No statistically significant differences were observed between the two techniques, at a confidence level of 95%. The reliability of the results obtained using the new method then enabled new methods to be developed for environmental applications such as the determination of atmospheric SO2 and NO2. The determination of NO2 in air employed the Griess-Saltzman (GS) reaction, in which a rosecolored product is formed that absorbs at a wavelength of 540 nm. Air sampling was performed using C18 cartridges impregnated with triethanolamine (TEA), at a flow rate of 0.5 L min-1 for 60 min. The analyte was solubilized using an alcoholic solution of methanol/water, and then transferred to a 10.0 mL volumetric flask containing 4.0 mL of the GS reagent. A 4.0 mL aliquot was placed on an acrylic surface and digital images of the solution were acquired using a scanner. Processing of the images then resulted in analytical signals that were proportional to the NO2 concentration. The detection limit was 12 ppb, the relative error was 7.0 %, and the coefficient of variation was 3.2 %. In order to improve the detection limit, the solution volume was optimized (300 μL) and a new procedure for acquisition and treatment of the digital images was implemented, resulting in a reduction...

Neste trabalho foram desenvolvidos métodos sensíveis, seletivos, de custo reduzido com potencial para serem utilizados em aplicações ambientais e tecnológicas. Os princípios utilizados para determinação destes de diferentes analitos são baseados em reações de soluções aquosas, que produzem espécies coloridas, utilizadas como base de métodos óticos, envolvendo a aquisição e o processamento de imagens digitais. Os experimentos mostraram a viabilidade da utilização de sensores ópticos de aquisição de imagens digitais em sensores CMOS e CCD. Como resultados preliminares foram comparados sinais analíticos obtidos por espectrofotômetro e imagens digitais para determinação de nitrito, fosfato inorgânico e ozônio residual em água. As diferentes determinações mostraram que os resultados não diferem entre si com índice de confiança de 95%. Os resultados obtidos nos procedimentos experimentais que resultaram em dados confiáveis foram base para que fossem estabelecidos novos métodos para aplicações ambientais, como a determinação de SO2 e NO2 atmosférico Para a determinação de NO2 em ar foi utilizada a reação Griess-Saltzman (GS) com formação de corante róseo com absorção em 540 nm. As amostragens de ar foram feitas utilizado um cartucho C18 impregnado com TEA (trietanolamina) com vazão de 0,5 L min-1 e tempo de 60 min. O analito foi solubilizado com solução alcoólica de metanol/ água e recolhido em balão de 10,0 mL contendo 4,0 mL do reagente GS. Uma alíquota de 4,0ml foi colocada em uma superfície de acrílico e a imagens da solução foi digitalizada com um scanner. O processamento das imagens obtidas resultou em sinais analíticos proporcionais ao NO2. O limite de detecção foi de 12 ppb, com um erro relativo de 7,0 % e coeficiente de variação de 3,2 %. Para melhorar o limite de detecção o volume de solução foi otimizado (300 μL) e novo...
Keywords: Quimica atmosferica; Imagens digitais; Alimentos - Analise; Atmospheric chemistry